The role of capitalism and colonialism in the deforestation of early modern Europe: Notes for historical land use models - Freg J. Stokes; Aleksandra Kaye; Patrick Roberts (Anthropocene, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

A comprehensive approach for detecting and locating black carbon in human placentae - Atsuo Chiu; Denise Ivey; Amanda Sanko; Barbara Tisdale; Philip J. Katzman; Thomas G. O’Connor; Kaye Thomas; Tanzy Love; Rogelio Perez-D’Gregorio; Carolyn M. Salafia; Richard K. Miller; Philip K. Hopke (Air Quality, Atmosphere & Health, 2026)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Use of quantitative PCR to detect and differentiate earthworm species - Nicole L. Schon; Pei-Chun (Lisa) Hsu; Sara M. (nee Kayes) Loeffen; Kyle Devey; Roger J. Hill (Applied Soil Ecology, 2025)

Palaeoecology of the Pliocene large carnivore guild at Hadar, Lower Awash Valley, Ethiopia - Joshua R. Robinson; Ignacio A. Lazagabaster; John Rowan; Margaret E. Lewis; Lars Werdelin; Christopher J. Campisano; Kaye E. Reed (Journal of Human Evolution, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Water quality impacts of recycling nutrients using organic fertilizers in circular agricultural scenarios - W. Lisenbee; A. Saha; P. Mohammadpour; R. Cibin; J. Kaye; C. Grady; I. Chaubey (Agricultural Systems, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Identifying predictors of translocation success in rare plant species - Joe Bellis; Oyomoare Osazuwa‐Peters; Joyce Maschinski; Matthew J. Keir; Elliott W. Parsons; Thomas N. Kaye; Michael Kunz; Jennifer Possley; Eric Menges; Stacy A. Smith; Daniela Roth; Debbie Brewer; et al. (Conservation Biology, 2024)
The fundamental goal of a rare plant translocation is to create self‐sustaining populations with the evolutionary resilience to persist in the long term. Yet, most plant translocation syntheses focus on a few factors influencing short‐term benchmarks of success (e.g., survival and reproduction). Short‐term benchmarks can be misleading when trying to infer future growth and viability because the factors that promote establishment may differ from those required for long‐term persistence. We assembled a large ( n = 275) and broadly representative data set of well‐documented and monitored (7.9 years on average) at‐risk plant translocations to identify the most important site attributes, management techniques, and species’ traits for six life‐cycle benchmarks and population metrics of translocation success. We used the random forest algorithm to quantify the relative importance of 29 predictor variables for each metric of success. Drivers of translocation outcomes varied across time frames and success metrics. Management techniques had the greatest relative influence on the attainment of life‐cycle benchmarks and short‐term population trends, whereas site attributes and species’ traits were more important for population persistence and long‐term trends. Specifically, large founder sizes increased the potential for reproduction and recruitment into the next generation, whereas declining habitat quality and the outplanting of species with low seed production led to increased extinction risks and a reduction in potential reproductive output in the long‐term, respectively. We also detected novel interactions between some of the most important drivers, such as an increased probability of next‐generation recruitment in species with greater seed production rates, but only when coupled with large founder sizes. Because most significant barriers to plant translocation success can be overcome by improving techniques or resolving site‐level issues through early intervention and management, we suggest that by combining long‐term monitoring with adaptive management, translocation programs can enhance the prospects of achieving long‐term success.

Non-avian dinosaur eggshell calcite can contain ancient, endogenous amino acids - Evan T. Saitta; Jakob Vinther; Molly K. Crisp; Geoffrey D. Abbott; Lucy Wheeler; Samantha Presslee; Thomas G. Kaye; Ian Bull; Ian Fletcher; Xinqi Chen; Daniel Vidal; Fernando Sanguino; et al. (Geochimica et Cosmochimica Acta, 2024)

Increased perivascular space volume in white matter and basal ganglia is associated with cognition in Parkinson’s Disease - Erin Kaye Donahue; Ryan Patrick Foreman; Jared Joshua Duran; Michael Walter Jakowec; Joseph O’Neill; Andrew J. Petkus; Daniel P. Holschneider; Jeiran Choupan; John Darrell Van Horn; Siva Venkadesh; Ece Bayram; Irene Litvan; et al. (Brain Imaging and Behavior, 2023)
Perivascular spaces (PVS), fluid-filled compartments surrounding brain vasculature, are an essential component of the glymphatic system responsible for transport of waste and nutrients. Glymphatic system impairment may underlie cognitive deficits in Parkinson’s disease (PD). Studies have focused on the role of basal ganglia PVS with cognition in PD, but the role of white matter PVS is unknown. This study examined the relationship of white matter and basal ganglia PVS with domain-specific and global cognition in individuals with PD. Fifty individuals with PD underwent 3T T1w magnetic resonance imaging (MRI) to determine PVS volume fraction, defined as PVS volume normalized to total regional volume, within (i) centrum semiovale, (ii) prefrontal white matter (medial orbitofrontal, rostral middle frontal, superior frontal), and (iii) basal ganglia. A neuropsychological battery included assessment of global cognitive function (Montreal Cognitive Assessment, and global cognitive composite score), and cognitive-specific domains (executive function, memory, visuospatial function, attention, and language). Higher white matter rostral middle frontal PVS was associated with lower scores in both global cognitive and visuospatial function. In the basal ganglia higher PVS was associated with lower scores for memory with a trend towards lower global cognitive composite score. While previous reports have shown that greater amount of PVS in the basal ganglia is associated with decline in global cognition in PD, our findings suggest that increased white matter PVS volume may also underlie changes in cognition.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Repurposing FDA-approved drugs as inhibitors of therapy-induced invadopodia activity in glioblastoma cells - Dylan Jones; Clarissa A. Whitehead; Marija Dinevska; Samuel S. Widodo; Liam M. Furst; Andrew P. Morokoff; Andrew H. Kaye; Katharine J. Drummond; Theo Mantamadiotis; Stanley S. Stylli (Molecular and Cellular Biochemistry, 2023)
Glioblastoma (GBM) is the most prevalent primary central nervous system tumour in adults. The lethality of GBM lies in its highly invasive, infiltrative, and neurologically destructive nature resulting in treatment failure, tumour recurrence and death. Even with current standard of care treatment with surgery, radiotherapy and chemotherapy, surviving tumour cells invade throughout the brain. We have previously shown that this invasive phenotype is facilitated by actin-rich, membrane-based structures known as invadopodia. The formation and matrix degrading activity of invadopodia is enhanced in GBM cells that survive treatment. Drug repurposing provides a means of identifying new therapeutic applications for existing drugs without the need for discovery or development and the associated time for clinical implementation. We investigate several FDA-approved agents for their ability to act as both cytotoxic agents in reducing cell viability and as ‘anti-invadopodia’ agents in GBM cell lines. Based on their cytotoxicity profile, three agents were selected, bortezomib, everolimus and fludarabine, to test their effect on GBM cell invasion. All three drugs reduced radiation/temozolomide-induced invadopodia activity, in addition to reducing GBM cell viability. These drugs demonstrate efficacious properties warranting further investigation with the potential to be implemented as part of the treatment regime for GBM.

Topography Mediates the Response of Soil CO2 Efflux to Precipitation Over Days, Seasons, and Years - Marissa Kopp; Jason Kaye; Yuting He Smeglin; Thomas Adams; Edward J. Primka; Brosi Bradley; Yuning Shi; David Eissenstat (Ecosystems, 2023)

Wastewater-based monitoring reveals geospatial-temporal trends for antibiotic-resistant pathogens in a large urban community - Zillur Rahman; Weijia Liu; Lara Stapleton; Nikki Kenters; Dewa A.P. Rasmika Dewi; Ori Gudes; Helen Ziochos; Stuart J. Khan; Kaye Power; Mary-Louise McLaws; Torsten Thomas (Environmental Pollution, 2023)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Design, Development, In Vitro and Preliminary In Vivo Evaluation of a Novel Photo-Angioplasty Device: Lumi-Solve - HongBin Liu; Gopal R. Sama; Andrea Robinson; Simon Mountford; Philip E. Thompson; Andrew Rodda; John Forsythe; Patrick J. Mornane; Paul Pasic; Helmut Thissen; Melissa Byrne; David M. Kaye; et al. (Cardiovascular Engineering and Technology, 2021)

Shared functional traits explain synchronous changes in long‐term count trends of migratory raptors - Patricia Kaye T. Dumandan; Keith L. Bildstein; Laurie J. Goodrich; Andrii Zaiats; T. Trevor Caughlin; Todd E. Katzner (Global Ecology and Biogeography, 2021)
Aim Assessing long‐term shifts in faunal assemblages is important to understand the consequences of ongoing global environmental change. One approach to assess drivers of assemblage changes is to identify the traits associated with synchronous shifts in count trends among species. Our research identified traits influencing trends in 73 years of count data on migrating raptors recorded in the north‐eastern USA. Location Pennsylvania, USA. Time period 1946–2018. Major taxa studied Birds of prey/raptors. Methods Migrating raptors were counted during autumn, following a standardized protocol. We used a hierarchical breakpoint model to identify when count trends shifted and to assess the role of traits in driving these trends before and after the breakpoint. Specifically, we quantified the probability of the direction (PD) of an effect of body mass, habitat or dietary specialization, migratory behaviour and susceptibility to dichlorodiphenyltrichloroethane (DDT) on count trends. Results We documented an assemblage‐wide mean shift in count trends of migrating raptors in 1974. In general, species that exhibited negative count trends before the breakpoint exhibited positive count trends afterwards. We found that traits associated with resource use (diet and habitat specialization) had high probabilities of affecting count trends, pre‐ and post‐breakpoint (> 90%). Moreover, the direction of their effects differed during both periods. Unexpectedly, other traits we evaluated, including DDT susceptibility, had relatively weaker associations with count trends. Main conclusions Trait‐based frameworks have promise for testing generalized assumptions about drivers of population trajectories. Historically, DDT was considered a key driver of changes in raptor population trends. However, our analysis suggests that other factors were also relevant. Moreover, the positive association between count trends and generalist behaviour depended on the temporal context. This result has implications for other settings where demographic trends can be linked to traits and help to identify drivers of biodiversity change.

COSORE: A community database for continuous soil respiration and other soil‐atmosphere greenhouse gas flux data - Ben Bond‐Lamberty; Danielle S. Christianson; Avni Malhotra; Stephanie C. Pennington; Debjani Sihi; Amir AghaKouchak; Hassan Anjileli; M. Altaf Arain; Juan J. Armesto; Samaneh Ashraf; Mioko Ataka; Dennis Baldocchi; et al. (Global Change Biology, 2020)
Globally, soils store two to three times as much carbon as currently resides in the atmosphere, and it is critical to understand how soil greenhouse gas (GHG) emissions and uptake will respond to ongoing climate change. In particular, the soil‐to‐atmosphere CO 2 flux, commonly though imprecisely termed soil respiration ( R S ), is one of the largest carbon fluxes in the Earth system. An increasing number of high‐frequency R S measurements (typically, from an automated system with hourly sampling) have been made over the last two decades; an increasing number of methane measurements are being made with such systems as well. Such high frequency data are an invaluable resource for understanding GHG fluxes, but lack a central database or repository. Here we describe the lightweight, open‐source COSORE (COntinuous SOil REspiration) database and software, that focuses on automated, continuous and long‐term GHG flux datasets, and is intended to serve as a community resource for earth sciences, climate change syntheses and model evaluation. Contributed datasets are mapped to a single, consistent standard, with metadata on contributors, geographic location, measurement conditions and ancillary data. The design emphasizes the importance of reproducibility, scientific transparency and open access to data. While being oriented towards continuously measured R S , the database design accommodates other soil‐atmosphere measurements (e.g. ecosystem respiration, chamber‐measured net ecosystem exchange, methane fluxes) as well as experimental treatments (heterotrophic only, etc.). We give brief examples of the types of analyses possible using this new community resource and describe its accompanying R software package.

Acute prazosin administration does not reduce stressor reactivity in healthy adults - Jesse T Kaye; Gaylen E Fronk; Aleksandra E Zgierska; Maireni R Cruz; David Rabago; John J Curtin (Psychopharmacology, 2019)

Sex differences in the association of alcohol with cognitive decline and brain pathology in a cohort of octogenarians - Casia Wardzala; Charles Murchison; Jennifer M. Loftis; Katie J. Schenning; Nora Mattek; Randall Woltjer; Jeff Kaye; Joseph F. Quinn; Clare J. Wilhelm (Psychopharmacology, 2018)

Fossil Giraffidae (Mammalia, Artiodactyla) from Lee Adoyta, Ledi-Geraru, and Late Pliocene Dietary Evolution in Giraffids from the Lower Awash Valley, Ethiopia - John Rowan; Ellis M. Locke; Joshua R. Robinson; Christopher J. Campisano; Jonathan G. Wynn; Kaye E. Reed (Journal of Mammalian Evolution, 2017)

A Diagnostic Decision Support System for BMP Selection in Small Urban Watershed - Yan Wang; Hubert J. Montas; Kaye L. Brubaker; Paul T. Leisnham; Adel Shirmohammadi; Victoria Chanse; Amanda K. Rockler (Water Resources Management, 2017)

A multi-lake study of seasonal variation in lake surface evaporation using MODIS satellite-derived surface temperature - R. C. Phillips; J. R. Saylor; N. B. Kaye; J. M. Gibert (Limnology, 2016)

Dissemination via the lymphatic or angiogenic route impacts the pathology, microenvironment and hypoxia-related drug response of lung metastases - Roben G. Gieling; Richard J. Fitzmaurice; Brian A. Telfer; Muhammad Babur; Kaye J. Williams (Clinical & Experimental Metastasis, 2015)

African Primate Assemblages Exhibit a Latitudinal Gradient in Dispersal Limitation - Lydia Beaudrot; Jason M. Kamilar; Andrew J. Marshall; Kaye E. Reed (International Journal of Primatology, 2014)

Forest succession, soil carbon accumulation, and rapid nitrogen storage in poorly remineralized soil organic matter - David Bruce Lewis; Michael J. Castellano; Jason P. Kaye (Ecology, 2014)
Substantial nitrogen (N) retention by temperate terrestrial ecosystems results from the rapid storage of newly deposited N in stable soil organic matter. Yet, we poorly understand the ecosystem properties that regulate the kinetics of this process. We applied mineral 15 N to temperate hardwood forest soils to test the hypothesis that N stabilization is faster owing to greater stocks of soil carbon (C) in late‐successional than in young forests. Within 26 minutes of addition, about 30% of tracer N was stored in stable form in organic‐horizon soil with a median residence time of >29 years. About 5–10% of tracer N was stored in a soluble organic form. An additional 30% of tracer N was recovered within hours from organic‐horizon soils in a remineralizable (labile) form, apparently derived from microbial biomass. Over the following year, tracer N storage in stable and soluble organic pools remained constant while recovery from labile and microbial pools declined. Tracer storage was greater in older forests with larger soil C pools, supporting our hypothesis that the accumulation of soil C with forest succession promotes ecosystem N retention. Rapid storage of stable soil N in the O horizon may create a source for chronic dissolved organic N losses from watersheds.

Eastern deciduous tree seedlings advance spring phenology in response to experimental warming, but not wetting, treatments - Margot W. Kaye; Rebekah J. Wagner (Plant Ecology, 2014)

Stand-replacing wildfires increase nitrification for decades in southwestern ponderosa pine forests - Valerie J. Kurth; Stephen C. Hart; Christopher S. Ross; Jason P. Kaye; Peter Z. Fulé (Oecologia, 2014)

Microclimate and ecological threshold responses in a warming and wetting experiment following whole tree harvest - M. D. McDaniel; R. J. Wagner; C. R. Rollinson; B. A. Kimball; M. W. Kaye; J. P. Kaye (Theoretical and Applied Climatology, 2014)

Climate change interactions affect soil carbon dioxide efflux and microbial functioning in a post-harvest forest - M. D. McDaniel; J. P. Kaye; M. W. Kaye; M. A. Bruns (Oecologia, 2014)

Cumulative geoecological effects of 62 years of infrastructure and climate change in ice‐rich permafrost landscapes, Prudhoe Bay Oilfield, Alaska - Martha K. Raynolds; Donald A. Walker; Kenneth J. Ambrosius; Jerry Brown; Kaye R. Everett; Mikhail Kanevskiy; Gary P. Kofinas; Vladimir E. Romanovsky; Yuri Shur; Patrick J. Webber (Global Change Biology, 2014)
Many areas of the Arctic are simultaneously affected by rapid climate change and rapid industrial development. These areas are likely to increase in number and size as sea ice melts and abundant Arctic natural resources become more accessible. Documenting the changes that have already occurred is essential to inform management approaches to minimize the impacts of future activities. Here, we determine the cumulative geoecological effects of 62 years (1949–2011) of infrastructure‐ and climate‐related changes in the Prudhoe Bay Oilfield, the oldest and most extensive industrial complex in the Arctic, and an area with extensive ice‐rich permafrost that is extraordinarily sensitive to climate change. We demonstrate that thermokarst has recently affected broad areas of the entire region, and that a sudden increase in the area affected began shortly after 1990 corresponding to a rapid rise in regional summer air temperatures and related permafrost temperatures. We also present a conceptual model that describes how infrastructure‐related factors, including road dust and roadside flooding are contributing to more extensive thermokarst in areas adjacent to roads and gravel pads. We mapped the historical infrastructure changes for the Alaska North Slope oilfields for 10 dates from the initial oil discovery in 1968–2011. By 2010, over 34% of the intensively mapped area was affected by oil development. In addition, between 1990 and 2001, coincident with strong atmospheric warming during the 1990s, 19% of the remaining natural landscapes (excluding areas covered by infrastructure, lakes and river floodplains) exhibited expansion of thermokarst features resulting in more abundant small ponds, greater microrelief, more active lakeshore erosion and increased landscape and habitat heterogeneity. This transition to a new geoecological regime will have impacts to wildlife habitat, local residents and industry.

Independent risk factors for the co-colonization of vancomycin-resistant Enterococcus faecalis and methicillin-resistant Staphylococcus aureus in the region most endemic for vancomycin-resistant Staphylococcus aureus isolation - K. Hayakawa; D. Marchaim; P. Bathina; E. T. Martin; J. M. Pogue; B. Sunkara; S. Kamatam; K. Ho; L. B. Willis; M. Ajamoughli; D. Patel; A. Khan; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Ecosystem Carbon Remains Low for Three Decades Following Fire and Constrains Soil CO2 Responses to Precipitation in Southwestern Ponderosa Pine Forests - Christopher S. Ross; Jason P. Kaye; Margot W. Kaye; Valerie J. Kurth; Rachel Brimmer; Stephen C. Hart; Peter Z. Fulé (Ecosystems, 2012)

Inversion of plant dominance–diversity relationships along a latitudinal stress gradient - Paul J. Richardson; Andrew S. MacDougall; Amanda G. Stanley; Thomas N. Kaye; Peter W. Dunwiddie (Ecology, 2012)
Species interactions affect plant diversity through the net effects of competition and facilitation, with the latter more prevalent in physically stressful environments when plant cover ameliorates abiotic stress. One explanation for species loss in invader‐dominated systems is a shift in the competition–facilitation balance, with competition intensifying in areas formerly structured by facilitation. We test this possibility with a 10‐site prairie meta‐experiment along a 500‐km latitudinal stress gradient, quantifying the relationships among abiotic stress, exotic dominance, and native plant recruitment over five years. The latitudinal gradient is inversely correlated with abiotic stress, with lower latitudes more moisture‐ and nutrient‐limited. We observed strong negative effects by invasive dominant grasses on plant establishment, but only in northern sites with lower‐stress environments. At these locations, disturbance was critical for recruitment by reducing the suppressive dominant (invasive) canopy. In more stressful environments to the south, the impacts of the dominant invaders on plant establishment became facilitative, and diversity was more limited by seed availability. Disturbance prevented recruitment because seedling survival depended on a protective plant canopy, presumably because the canopy reduced temperature or moisture stress. Seed limitation was similarly prevalent in all sites. Our work confirms the importance of facilitation as an organizing process for plants in higher‐stress environments, even with transformations of species composition and dominance. It also demonstrates that the mechanisms regulating diversity, including invader impacts, can vary within the same plant community depending on environmental context. Because limits on native plant recruitment are environmentally contingent, management strategies that seek to increase diversity, including invader eradication, must account for site‐level variations in the balance between biotic and abiotic constraints.

Random local temporal structure of category fluency responses - David J. Meyer; Jason Messer; Tanya Singh; Peter J. Thomas; Wojbor A. Woyczynski; Jeffrey Kaye; Alan J. Lerner (Journal of Computational Neuroscience, 2012)

Matrix population models from 20 studies of perennial plant populations - Martha M. Ellis; Jennifer L. Williams; Peter Lesica; Timothy J. Bell; Paulette Bierzychudek; Marlin Bowles; Elizabeth E. Crone; Daniel F. Doak; Johan Ehrlén; Albertine Ellis-Adam; Kathryn McEachern; Rengaian Ganesan; et al. (Ecology, 2012)
Demographic transition matrices are among the most commonly applied population models for both basic and applied ecological research. The relatively simple framework of these models and simple, easily interpretable summary statistics they produce have prompted the wide use of these models across an exceptionally broad range of taxa. Here, we provide annual transition matrices and observed stage structures/population sizes for 20 perennial plant species which have been the focal species for long‐term demographic monitoring. These data were assembled as part of the “Testing Matrix Models” working group through the National Center for Ecological Analysis and Synthesis (NCEAS). The data represent 82 populations with >460 total population‐years of observations. It is our hope that making these data available will help promote and improve our ability to monitor and understand plant population dynamics. The complete data sets corresponding to abstracts published in the Data Papers section of the journal are published electronically in Ecological Archives at 〈 http://esapubs.org/archive 〉. (The accession number for each Data Paper is given directly beneath the title.)

Linking Carbon Saturation Concepts to Nitrogen Saturation and Retention - Michael J. Castellano; Jason P. Kaye; Henry Lin; John P. Schmidt (Ecosystems, 2012)

Decomposition of urban atmospheric carbon in Sonoran Desert soils - Jason P. Kaye; Sara E. Eckert; Daniel A. Gonzales; Jonathan O. Allen; Sharon J. Hall; Ryan A. Sponseller; Nancy B. Grimm (Urban Ecosystems, 2011)

Hydrological and biogeochemical controls on the timing and magnitude of nitrous oxide flux across an agricultural landscape - MICHAEL J. CASTELLANO; JOHN P. SCHMIDT; JASON P. KAYE; CHARLES WALKER; CHRIS B. GRAHAM; HENRY LIN; CURTIS J. DELL (Global Change Biology, 2010)
Anticipated increases in precipitation intensity due to climate change may affect hydrological controls on soil N 2 O fluxes, resulting in a feedback between climate change and soil greenhouse gas emissions. We evaluated soil hydrologic controls on N 2 O emissions during experimental water table fluctuations in large, intact soil columns amended with 100 kg ha −1 KNO 3 ‐N. Soil columns were collected from three landscape positions that vary in hydrological and biogeochemical properties ( N = 12 columns). We flooded columns from bottom to surface to simulate water table fluctuations that are typical for this site, and expected to increase given future climate change scenarios. After the soil was saturated to the surface, we allowed the columns to drain freely while monitoring volumetric soil water content, matric potential and N 2 O emissions over 96 h. Across all landscape positions and replicate soil columns, there was a positive linear relationship between total soil N and the log of cumulative N 2 O emissions ( r 2 = 0.47; P = 0.013). Within individual soil columns, N 2 O flux was a Gaussian function of water‐filled pore space (WFPS) during drainage (mean r 2 = 0.90). However, instantaneous maximum N 2 O flux rates did not occur at a consistent WFPS, ranging from 63% to 98% WFPS across landscape positions and replicate soil columns. In contrast, instantaneous maximum N 2 O flux rates occurred within a narrow range (−1.88 to −4.48 kPa) of soil matric potential that approximated field capacity. The relatively consistent relationship between maximum N 2 O flux rates and matric potential indicates that water filled pore size is an important factor affecting soil N 2 O fluxes. These data demonstrate that matric potential is the strongest predictor of the timing of N 2 O fluxes across soils that differ in texture, structure and bulk density.

Global Within-Site Variance in Soil Solution Nitrogen and Hydraulic Conductivity Are Correlated with Clay Content - Michael J. Castellano; Jason P. Kaye (Ecosystems, 2009)

Root nodule bacteria isolated from South African Lotononis bainesii, L. listii and L. solitudinis are species of Methylobacterium that are unable to utilize methanol - Julie Kaye Ardley; Graham W. O’Hara; Wayne G. Reeve; Ron J. Yates; Michael J. Dilworth; Ravi P. Tiwari; John G. Howieson (Archives of Microbiology, 2009)

Long‐term impact of a stand‐replacing fire on ecosystem CO 2 exchange of a ponderosa pine forest - S. DORE; T. E. KOLB; M. MONTES‐HELU; B. W. SULLIVAN; W. D. WINSLOW; S. C. HART; J. P. KAYE; G. W. KOCH; B. A. HUNGATE (Global Change Biology, 2008)
Ponderosa pine ( Pinus ponderosa ) forests of the southwestern United States are a mosaic of stands where undisturbed forests are carbon sinks, and stands recovering from wildfires may be sources of carbon to the atmosphere for decades after the fire. However, the relative magnitude of these sinks and sources has never been directly measured in this region, limiting our understanding of the role of fire in regional and US carbon budgets. We used the eddy covariance technique to measure the CO 2 exchange of two forest sites, one burned by fire in 1996, and an unburned forest. The fire was a high‐intensity stand‐replacing burn that killed all trees. Ten years after the fire, the burned site was still a source of CO 2 to the atmosphere [109±6 (SEM) g C m −2 yr −1 ], whereas the unburned site was a sink (−164±23 g C m −2 yr −1 ). The fire reduced total carbon storage and shifted ecosystem carbon allocation from the forest floor and living biomass to necromass. Annual ecosystem respiration was lower at the burned site (480±5 g C m −2 yr −1 ) than at the unburned site (710±54 g C m −2 yr −1 ), but the difference in gross primary production was even larger (372±13 g C m −2 yr −1 at the burned site and 858±37 g C m −2 yr −1 at the unburned site). Water availability controlled carbon flux in the warm season at both sites, and the burned site was a source of carbon in all months, even during the summer, when wet and warm conditions favored respiration more than photosynthesis. Our study shows that carbon losses following stand‐replacing fires in ponderosa pine forests can persist for decades due to slow recovery of the gross primary production. Because fire exclusion is becoming increasingly difficult in dry western forests, a large US forest carbon sink could shift to a decadal‐scale carbon source.

F2-Isoprostanes as Biomarkers of Late-onset Alzheimer’s Disease - Thomas J. Montine; Joseph Quinn; Jeffrey Kaye; Jason D. Morrow (Journal of Molecular Neuroscience, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

The availability of nitrogen from sugarcane trash on contrasting soils in the wet tropics of North Queensland - Elizabeth A. Meier; Peter J. Thorburn; Malcolm K. Wegener; Kaye E. Basford (Nutrient Cycling in Agroecosystems, 2006)

Carbon fluxes, nitrogen cycling, and soil microbial communities in adjacent urban, native and agricultural ecosystems - J. P. Kaye; R. L. McCulley; I. C. Burke (Global Change Biology, 2005)
Urban ecosystems are expanding globally, and assessing the ecological consequences of urbanization is critical to understanding the biology of local and global change related to land use. We measured carbon (C) fluxes, nitrogen (N) cycling, and soil microbial community structure in a replicated ( n =3) field experiment comparing urban lawns to corn, wheat–fallow, and unmanaged shortgrass steppe ecosystems in northern Colorado. The urban and corn sites were irrigated and fertilized. Wheat and shortgrass steppe sites were not fertilized or irrigated. Aboveground net primary productivity (ANPP) in urban ecosystems (383±11 C m −2 yr −1 ) was four to five times greater than wheat or shortgrass steppe but significantly less than corn (537±44 C m −2 yr −1 ). Soil respiration (2777±273 g C m −2 yr −1 ) and total belowground C allocation (2602±269 g C m −2 yr −1 ) in urban ecosystems were both 2.5 to five times greater than any other land‐use type. We estimate that for a large (1578 km 2 ) portion of Larimer County, Colorado, urban lawns occupying 6.4% of the land area account for up to 30% of regional ANPP and 24% of regional soil respiration from land‐use types that we sampled. The rate of N cycling from urban lawn mower clippings to the soil surface was comparable with the rate of N export in harvested corn (both ∼12–15 g N m −2 yr −1 ). A one‐time measurement of microbial community structure via phospholipid fatty acid analysis suggested that land‐use type had a large impact on microbial biomass and a small impact on the relative abundance of broad taxonomic groups of microorganisms. Our data are consistent with several other studies suggesting that urbanization of arid and semiarid ecosystems leads to enhanced C cycling rates that alter regional C budgets.

Targeted mapping of a sugarcane rust resistance gene (Bru1) using bulked segregant analysis and AFLP markers - C. Asnaghi; D. Roques; S. Ruffel; C. Kaye; J.-Y. Hoarau; H. Télismart; J. C. Girard; L. M. Raboin; A. M. Risterucci; L. Grivet; A. D’Hont (Theoretical and Applied Genetics, 2004)

Application of synteny across Poaceae to determine the map location of a sugarcane rust resistance gene - C. Asnaghi; F. Paulet; C. Kaye; L. Grivet; M. Deu; J. C. Glaszmann; A. D’Hont (Theoretical and Applied Genetics, 2000)

FatalLegionella longbeachae infection following heart transplantation - T. M. Korman; A. Fuller; J. Ibrahim; D. Kaye; P. Bergin (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

The effects of increasing CO 2 and temperature on oak leaf palatability and the implications for herbivorous insects - S. J. Dury; J. E. G. Good; C. M. Perrins; A. Buse; T. Kaye (Global Change Biology, 1998)
Rising levels of atmospheric CO 2 are expected to perturb forest ecosystems, although the extent to which specific ecological interactions will be modified is unclear. This research evaluates the effects of elevated CO 2 and temperature, alone and in combination, on the leaf nutritional quality of Pendunculate oak ( Quercus robur L. ), and the implications for herbiverous insect defoliators are discussed. A 3 °C temperature rise reduced leaf nutritional quality, by reducing foliar nitrogen concentration and increasing condensed tannin content. Doubling atmospheric CO 2 temporarily increased total phenolics, but also reduced leaf toughness. The nutritional quality of the second leaf flush (lammas growth) was considerably reduced at elevated CO 2 . It is concluded that larval development of spring‐feeding defoliators and hence adult fecundity may be adversely affected by increased temperatures.

Molecular characterization of a bean α-amylase inhibitor that inhibits the α-amylase of the Mexican bean weevil Zabrotes subfasciatus - M. Fatima Grossi de Sa; T. Erik Mirkov; Masao Ishimoto; Gabriella Colucci; Kaye S. Bateman; Maarten J. Chrispeels (Planta, 1997)

In Vivo Gene Transfer by Intravenous Administration of Stable Cationic Lipid/DNA Complex - Hans E. J. Hofland; Dea Nagy; Jing-Jie Liu; Kaye Spratt; Ya-Li Lee; Olivier Danos; Sean M. Sullivan (Pharmaceutical Research, 1997)